Cyber Counseling Sebagai Metode Meningkatkan Layanan Bimbingan dan Konseling di Sekolah: Literature Review - Adela, Nurul; N, Neviyarni; Nirwana, Herman (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Guidance and counseling services play a crucial role in supporting students’ academic, social, and emotional development. With technological advances, counseling services can now be conducted online through cyber counseling. This study aims to discuss the implementation stages, media, effectiveness, and limitations of cyber counseling in schools. Using a literature review method, it was found that cyber counseling consists of three main stages: preparation, counseling process, and post-counseling. Various media, such as email, phone, chat, and video conferencing, are used to support this service. Although effective in reaching students who find it difficult to meet counselors in person, cyber counseling faces several challenges, particularly in terms of empathy and technical limitations. This study concludes that cyber counseling is a valuable alternative, provided that appropriate technology use and stable internet connection are ensured.